ETIKA PERIKLANAN BERBASIS KONTEN SYARIAH: Studi Aturan Pemasangan Reklame Di Meulaboh Aceh Barat - Rindi Purnama Putra; Irsan Adrianda (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
This study examines ethics in advertising, especially what we want to see are aspects related to Islamic content-based advertising ethics. This is important to study because, it is not uncommon for problems to arise regarding advertising ethics. Where ads that are displayed are often considered to give the impression and messages that ignore ethical norms and values. So this study tries to see how the normative rules that regulate advertising content in West Aceh, taking into account all aspects of local wisdom based on Islamic sharia, so that the display of advertisements displayed is not only different from the appearance of advertisements in other regions in Indonesia, but also accommodates the value of-locality value.